2006
DOI: 10.1107/s1744309106041467
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification, crystallization and preliminary X-ray diffraction analysis of mitochondrial thioredoxin Trx3 fromSaccharomyces cerevisiae

Abstract: There are three thioredoxin isoforms in the yeast Saccharomyces cerevisiae: two cytosolic/nuclear thioredoxins, Trx1 and Trx2, and one mitochondrial thioredoxin, Trx3. In the present work, S. cerevisiae Trx3 overexpressed in Escherichia coli was purified and crystallized. The Trx3 crystals were obtained by the hanging-drop vapour-diffusion method. A data set diffracting to 2.0 A resolution was collected from a single crystal. The crystal belongs to space group P3(1), with unit-cell parameters a = b = 49.57, c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2009
2009

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…The structures of S. cerevisiae Trx2 and Trx3 have recently been determined by our group. The space groups of Trx2 and Trx3 are P4 1 2 1 2 and P3 1 , with unit-cell parameters a = b = 83.15, c = 64.73 Å , = = = 90 (Bao et al, 2007) and a = b = 49.57, c = 94.55 Å , = = 90, = 120 (Bao et al, 2006), respectively. The data set for Trx1 was indexed in space group P2 1 2 1 2 1 and calculation of the Matthews coefficient ($2.15 Å 3 Da À1 ) indicated that there is only one molecule in the asymmetric unit (Collaborative Computational Project, Number 4, 1994), with a solvent content of 61.3%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures of S. cerevisiae Trx2 and Trx3 have recently been determined by our group. The space groups of Trx2 and Trx3 are P4 1 2 1 2 and P3 1 , with unit-cell parameters a = b = 83.15, c = 64.73 Å , = = = 90 (Bao et al, 2007) and a = b = 49.57, c = 94.55 Å , = = 90, = 120 (Bao et al, 2006), respectively. The data set for Trx1 was indexed in space group P2 1 2 1 2 1 and calculation of the Matthews coefficient ($2.15 Å 3 Da À1 ) indicated that there is only one molecule in the asymmetric unit (Collaborative Computational Project, Number 4, 1994), with a solvent content of 61.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the crystal structures of Trx2 and Trx3 from the yeast S. cerevisiae have been solved by our group (Bao et al, 2006(Bao et al, , 2007. In the present work, we report the crystallization and preliminary X-ray diffraction analysis of the last thioredoxin, Trx1, the structure of which remains unknown.…”
Section: Introductionmentioning
confidence: 85%
“…Recently, the crystal structures of three isoforms of Trx from Saccharomyces cerevisiae have been solved by our group (Bao et al, 2006(Bao et al, , 2007Zhang et al, 2008). Here, we report the crystallization and preliminary X-ray diffraction analysis of glutathionylated Trx1 C33S mutant (Trx1C33S-SG), which should present the transient mixeddisulfide state of Trx1 Cys30 with GSH as described above.…”
Section: Introductionmentioning
confidence: 91%
“…Posteriormente, Pedrajas et al (1999) As estruturas cristalográficas das três tiorredoxinas, ScTrx1 (Zhang et al, 2008), ScTrx2 (Bao et al, 2007) e ScTrx3 (Bao et al, 2006) (Amorim et al, 2007) obtidas por RMN em solução. A ScTrx1 possui 76% de identidade e 87% de similaridade quando comparada á ScTrx2.…”
Section: Os Sistemas Tiorredoxina Em Saccharomyces Cerevisiaeunclassified